Analisis Hubungan Faktor-Faktor Dining Experience dalam Menciptakan Minat Beli Ulang di Café Le Jardin Kabupaten Lahat Provinsi Sumatera Selatan - Andhika Chandra Lesmana; Samuel Hamonangan; Nur Shabrina Reznani; Raty Rusmiana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2026)
The growth of the café business annually ranges between 15–20%, indicating that this industry has significant potential and encourages entrepreneurs to start businesses in the food and beverage sector. From a business perspective, cafés and restaurants have become one of the most attractive industries for entrepreneurs in Indonesia due to the vast opportunities and consistent market demand. This can be observed through the increasing number of coffee shops and the rising level of domestic coffee consumption. South Sumatra is one of the provinces in Indonesia that has experienced significant growth in coffee shops, commonly known as cafés. On average, each coffee shop provides a comfortable atmosphere that encourages visitors to stay longer, supported by unique and Instagrammable designs that add value and are expected to attract customers to visit and return to the establishment. When consumers visit a restaurant or café, they expect to receive the best products and services. Davis, Lockwood, Alcott, and Pantelidis (2008) stated that when consumers dine in a restaurant or café, they undergo a dining experience that begins when they arrive at the establishment and continues until they leave the venue. This study employed a descriptive research design using a quantitative approach. Data were collected through questionnaires, observations, interviews, documentation, and literature review. The population of this study consisted of all consumers who were currently experiencing or had previously experienced a dining experience at Le Jardin Café, Lahat Regency. A total of 100 respondents were selected as the research sample. The results of this study indicate that the t-test results show a mean score greater than 3, and the calculated t-value is higher than the t-table value. These findings conclude that consumers have positive perceptions of the Dining Experience and Repurchase Intention variables at Le Jardin Café, Lahat Regency. Meanwhile, the correlation results show that all indicators of the Dining Experience and Repurchase Intention variables have positive relationships; however, the relationships are not strong.